2006
DOI: 10.1080/00071660601040079
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplements of selenium, vitamin E or combinations of the two on antibody responses of broilers

Abstract: 1. The effects of selenium and vitamin E supplementation on some immune parameters were investigated in broilers. 2. Broiler chicks were fed on maize-soybean diets with different concentrations of vitamin E (0-200 mg/kg) and selenium (0-0.2 mg/kg diet) either alone or in combinations from 1 to 42 d of age. 3. Chicks were immunised against Newcastle disease virus (NDV) vaccine at 21 d of age and haemagglutination inhibition (HI) titres were determined after 10 d. 4. Chicks receiving supplements of 200 mg vitami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
35
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 25 publications
8
35
1
1
Order By: Relevance
“…Previous report demonstrated that increased Se levels from 0.10 to 0.25 mg/kg markedly increased broiler weight and reduced feed efficiency ratio, where diet premixes were prepared without Se and vitamin E (Singh et al, 2006). In the presChen et al Se increased broiler oxidation resistance ent study, the broiler production performance were not significantly improved when supplemented with 0.3, 0.5, 1.0 or 2.0 mg/kg organic selenium, which was in agreement with other reports (Swain et al, 2000;Yoon et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Previous report demonstrated that increased Se levels from 0.10 to 0.25 mg/kg markedly increased broiler weight and reduced feed efficiency ratio, where diet premixes were prepared without Se and vitamin E (Singh et al, 2006). In the presChen et al Se increased broiler oxidation resistance ent study, the broiler production performance were not significantly improved when supplemented with 0.3, 0.5, 1.0 or 2.0 mg/kg organic selenium, which was in agreement with other reports (Swain et al, 2000;Yoon et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin E supplemented to diets at a level of 200 mg kg -1 diet increases the response of primary and secondary antibodies in broilers subjected to high temperatures (Singh et al, 2006;Niu et al, 2009). Habibian et al (2014) observed that besides the increase in antibody responses, there was a decrease in the heterophil/lymphocyte ratio, reduced HDL and increased LDL in broiler under heat stress, supplemented with vitamin E at 250 mg/kg feed, with or without the combined addition of organic selenium, showing the pronounced effect of this vitamin.…”
Section: Referencesmentioning
confidence: 99%
“…In general, erythrocytes and lymphoid organs originate from the common pluripotent stem cells. When Se was supplemented in the diet, weights of the bursa and spleen increased in broiler chickens (Singh et al, 2006). The spleen of chicken is a mixed lymphatic tissue, having both the T-and B-cell rejoins, and these data suggest that these rejoins were enhanced by Se-enriched JRS.…”
Section: Discussionmentioning
confidence: 71%